TRADITIONAL GAME OF JUMPING ROPE IN DEVELOPING GROSS MOTOR SKILLS OF EARLY CHILDHOOD - Megawati, Reyzah; Jamil, Zawaqi Afdal; Jamilah, Jamilah (STAH Dharma Sentana Sulawesi Tengah, 2023)
The purpose of this study was to analyze and describe the lack of application of traditional game concepts to develop children's gross motor skills in the learning process. The research method uses a descriptive qualitative method. Data collection is done by observation, interviews and documentation. Data analysis uses the Miles and Huberman model, namely data reduction, data presentation, data verification and trust test using data triangulation. The results of this study are that the concept of gross motor development in the learning system at Kindergarten Melati II Telanaipura can be said to be good, due to the assistance of the habituation activity method carried out by the teacher. The concept of applying traditional games in developing gross motor skills at Kindergarten Melati II Telanaipura can also be said to be optimal with the help of teachers and directions from teachers. Although there are inhibiting factors in carrying out the jump rope game, namely from the environment and parents.